Neural Networks: A Pattern Recognition Perspective - Bishop, Christopher (Handbook of Neural Computation, 1996)
The majority of current applications of neural networks are concerned with problems in pattern recognition. In this article we show how neural networks can be placed on a principled, statistical foundation, and we discuss some of the practical benefits which this brings.